(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
This study was carried out to investigate the occurrence of various surgical affections often encountered in carnivorous zoo animals of National Zoological Garden, Dhaka, Bangladesh. The study was based on the surgical cases reported in the day record book maintained by the zoo authority during the period of January - December 2012 to January - December 2016. Of 74 surgically affected zoo carnivore’s cases; Felididae recorded highest 81.08 %, Canidae 12.61 % and, Ursidae 6.76 %. When affections were compared between sexes, it was observed higher in male 62.16 % than in female 37.84 %. Among the different surgical affections; the wound cases were observed at the apex with 29.7 % and 18.9 %, followed by paralysis 10.08 % and 6.8 %, skin injury 9.5 % and 6.8 %, myiasis 4.1 % and 2.7 %, lameness 2.7 % and 4.1 % in male and female, respectively. While, tail sore 1.4 %, conjunctivitis 1.4 % and hoof injury 1.4 % were observed in male carnivores only. In conclusion, this report signifies the common surgical affections suffered by zoo carnivores, while male carnivores showed comparatively more prone to affections than female one. This report may be helpful to develop a control strategy in managing zoo animal captivity and further minimizing these surgical affections. Res. Agric., Livest. Fish.5(3): 335-339, December 2018